2010
DOI: 10.21608/ejabf.2010.2050
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Bacteriological properties of fresh and frozen sold cephalopods in the Egyptian market.

Abstract: ABSTRACTarious cephalopods are available for seafood consumers in the Suez Canal area either caught from the Suez Canal and stored in ice during transporting and marketing or imported and sold frozen in retail market. The lower price of imported cephalopods compared with the fresh ones makes it more demanded by consumers, restaurants and hotels. The objective of this study is to evaluate the quality and safety of fresh/chilled squid (Uroteuthis duvauceli) and cuttlefish (Sepia pharaonis) compared to frozen imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…The fatty acid profiles (as relative percentage of total fatty acids) are in accordance to other previous studies concerning L. duvaucelii from Thailand (SFA 41.3%, MUFA 14.1% and PUFA 44.7%; Chedoloh et al, 2011) and Egypt (SFA 44.6%, MUFA 6.7% and PUFA 48.7%; Gabr, 2010), L. vulgaris from the Mediterranean Sea (SFA 32.9%, MUFA 9.4% and PUFA 57.3% (Miliou et al, 2006); SFA 35.7%, MUFA 9.0% and PUFA 51.1% (Navarro and Villanueva, 2000); SFA 31.8-35.3%, MUFA 7.3-8.1% and PUFA 52.8-55.9% (Ozogul et al, 2008); SFA 36.8%, MUFA 7.4% and PUFA 51.1% (Salman et al, 2007)) and L. gahi caught in Falkland Islands (SFA 27.6%, MUFA 8.8% and PUFA 61.1% (Norambuena et al, 2012); SFA 30.9%, MUFA 13.6% and PUFA 55.2% (Phillips et al, 2003)). No complete profile description was found for L. opalescens (Tziouveli et al, 2011) and no data was found for L. reynaudii.…”
supporting
confidence: 91%
“…The fatty acid profiles (as relative percentage of total fatty acids) are in accordance to other previous studies concerning L. duvaucelii from Thailand (SFA 41.3%, MUFA 14.1% and PUFA 44.7%; Chedoloh et al, 2011) and Egypt (SFA 44.6%, MUFA 6.7% and PUFA 48.7%; Gabr, 2010), L. vulgaris from the Mediterranean Sea (SFA 32.9%, MUFA 9.4% and PUFA 57.3% (Miliou et al, 2006); SFA 35.7%, MUFA 9.0% and PUFA 51.1% (Navarro and Villanueva, 2000); SFA 31.8-35.3%, MUFA 7.3-8.1% and PUFA 52.8-55.9% (Ozogul et al, 2008); SFA 36.8%, MUFA 7.4% and PUFA 51.1% (Salman et al, 2007)) and L. gahi caught in Falkland Islands (SFA 27.6%, MUFA 8.8% and PUFA 61.1% (Norambuena et al, 2012); SFA 30.9%, MUFA 13.6% and PUFA 55.2% (Phillips et al, 2003)). No complete profile description was found for L. opalescens (Tziouveli et al, 2011) and no data was found for L. reynaudii.…”
supporting
confidence: 91%